2017
DOI: 10.3390/ijerph14070703
|View full text |Cite
|
Sign up to set email alerts
|

Health-Promoting Nature Access for People with Mobility Impairments: A Systematic Review

Abstract: This study systematically evaluated the scientific evidence for health benefits of natural environments for people with mobility impairments. Literature searches based on five categories of terms—target group, nature type, health-related impacts, nature-related activities and accessibility issues—were conducted in four databases (Web of Science, Scopus, CAB ABSTRACT and Medline). Twenty-seven articles from 4196 hits were included in the systematic reviews. We concluded that people with mobility disabilities co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 33 publications
3
56
0
Order By: Relevance
“…Studies have found that this group has the same preference for green spaces as the able-bodied reference group, shares the same environmental attitudes (Brown, Kaplan & Quaderer 1999;Lovelock 2010;Moore, Dattilo & Devine 1996), and gains the same health benefits. (Zhang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that this group has the same preference for green spaces as the able-bodied reference group, shares the same environmental attitudes (Brown, Kaplan & Quaderer 1999;Lovelock 2010;Moore, Dattilo & Devine 1996), and gains the same health benefits. (Zhang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…e high number of primary studies in the last 10 years reflects the increasing interest by the researchers and public health professionals in this area; however, a major limitation of this evidence is more than 50% of the included studies were cross-sectional; in these studies, the temporal relationship between exposure and outcome cannot be established [51]; therefore, it is not possible to conclude the causality of the built environment on mental health [47]. Hence, as mentioned in some SRs [48,49,52], there is a need for more high-quality research, especially controlled longitudinal/time-series analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Drawbacks in the critical items included: the SRs did not state prior design or registered protocol [15, 43, 45-48, 51, 52], did not include list of excluded studies with reasons [15, 43-48, 51, 52], and did not address the risk of bias in the individual studies [15, 43-45, 47, 52]. Drawbacks in the noncritical items included: the authors did not report on the sources of funding for the studies included in the SRs [15,[43][44][45][46][47][48][49][50][51][52], and the SRs did not report conflicts of interest [43,47]. e kappa coefficient for the total AMSTAR-2 score showed substantial agreement (0.78; 95% confidence interval (CI) 0.67-0.88).…”
Section: Characteristics and Quality Of The Systematic Reviewsmentioning
confidence: 99%
See 2 more Smart Citations